Environment influence on the yield of corn originated from different methods - Ruschel, Renato (Pesquisa Agropecuaria Brasileira, 2014)
Twenty five different hybrids, synthetics, varieties and populations of corn, were analyzed by their yields as well as their yield variation due to the environment conditions. A total of ten experiments were conducted in a uniform way in the Brazilian States of São Paulo, Rio de Janeiro and Espírito Santo, during two years in six localities situated between the latitudes of 22°52' and 19°25' South and altitudes from the sea level to 815 meters above it. In order to make a comparision of the yield variability of the different kinds of corn, among the different localities, years and climatic zones, were used components of variance due to the interactions obtained in the analysis of the experiments in group. The results showed: 1. The traditional varieties showed lower production than the other ones. 2. The average yields of the populations were excellent, being good material for selection. The populations WP 12, WP 13 and WP 9 showed better yields than the hybrids average in the tropical region. 3. The synthetics showed the greatest productivity in the region where they had been originated. From the results, conclusions were made about the largeness of the area with possibilities of using corn originated from different methods of improvement.